Indium‐111 labeling of high‐density lipoprotein‐mimicking phospholipid‐styrene maleic acid copolymer complexes and its biodistribution in mice. (20th July 2018) - Tanaka, Masafumi; Hosotani, Akira; Mukai, Takahiro
Abstract : Discoidal lipid nanoparticles mimicking native high‐density lipoproteins (HDL) are promising delivery vehicles of drugs and/or imaging agents. However, little is known about the in vivo biodistribution of such discoidal lipid nanoparticles compared to liposomes, clinically available spherical lipid nanoparticles. Recently, it has been reported that synthetic polymers instead of apolipoproteins can be complexed with phospholipid to form discoidal nanoparticles. In the present study, with the aim of developing phospholipid‐synthetic polymer complexes for future clinical applications, the biodistribution of such particles in normal mice was investigated. Lipid nanoparticles comprising 1‐palmitoyl‐2‐oleoyl‐glycero‐3‐phosphocholine (POPC) and styrene maleic acid copolymer (SMA), having sizes similar to native HDL, were prepared using the freeze‐sonication method. POPC‐SMA complexes remained stable at 37°C for at least 3 days in buffer. By devising ways to avoid detrimental effects accompanied by pH reduction and nonspecific binding of 111 In to SMA, POPC‐SMA complexes were successfully labeled with 111 In without affecting particle integrity. The biodistribution of POPC‐SMA complexes in normal mice was similar to that of discoidal lipid nanoparticles composed of POPC and apolipoprotein A‐I, the major protein constituent of native HDL. Unlike liposomes, the accumulation of POPC‐SMA complexes in the spleen was low, suggesting that these complexes are not recognized as foreign substances. To the best of our knowledge, this is the first in vivo study of HDL‐mimicking phospholipid‐synthetic polymer complexes. Abstract : Discoidal lipid nanoparticles comprising 1‐palmitoyl‐2‐oleoyl‐glycero‐3‐phosphocholine (POPC) and styrene maleic acid copolymer (SMA) were successfully labeled with 111In. The biodistribution of POPC–SMA complexes in normal mice was similar to that of discoidal lipid nanoparticles composed of POPC and apolipoprotein A‐I, the major protein constituent of native high‐density lipoprotein (HDL). To the best of our knowledge, this is the first in vivo study of HDL‐mimicking phospholipid‐synthetic polymer complexes.